Leisure‐Time Sedentary Behavior and Obesity Among 116, 762 Adolescents Aged 12‐15 Years from 41 Low‐ and Middle‐Income Countries. Issue 5 (11th March 2019) - Ashdown‐Franks, Garcia; Vancampfort, Davy; Firth, Joseph; Veronese, Nicola; Jackson, Sarah E.; Smith, Lee; Stubbs, Brendon; Koyanagi, Ai
Abstract : Objective: Rates of adolescent obesity are increasing worldwide, with steeper increases being observed in low‐ and middle‐income countries (LMICs). Sedentary behavior (SB) has been associated with various physical and mental health conditions. Little is known about the association between SB and obesity among adolescents in LMICs. This cross‐sectional study explored the associations between SB and obesity in adolescents from 41 LMICs. Methods: Obesity was measured using BMI; SB was assessed through self‐report and was considered for all times except when subjects were at school or doing homework. Results: Data from the Global School‐based Student Health Survey were analyzed in 116, 762 adolescents (mean [SD] age 13.8 [1.0] years; 48.6% female). The overall prevalence of obesity was 4%, and the prevalence of ≥ 3 h/d of SB was 26%. The prevalence of obesity and SB were lowest in low‐income countries and highest in upper‐middle‐income countries. SB for ≥ 3 h/d was associated with higher odds of obesity in 32 countries. This relationship was strongest among low‐income countries. Conclusions: Being sedentary for ≥ 3 h/d is associated with increased odds of obesity in adolescence. Future longitudinal data are required to confirm these findings and to inform interventions targeting SB among adolescents in LMICs, thereby reducing the prevalence of obesity.